Static performance of agglomerated CNT-reinforced porous plates bonded with piezoceramic faces - Moradi-Dastjerdi, Rasool; Behdinan, Kamran; Safaei, Babak; Qin, Zhaoye (Pergamon-Elsevier Science Ltd, 2020)
Bonding the upper and lower faces of a nanocomposite porous plate with piezoceramics eventuates a smart multidisciplinary plate (SMP). In the current work, the deflection and stress responses of such SMP5 under static electrical voltages and mechanical loads have been presented. The middle plate of SMP is assumed to have simultaneous functionally graded (FG) dispersions of pore and nanofiller along the thickness. The enhancement parts of the nanocomposite material are assumed to be carbon nanotubes (CNTs) and their agglomerations with random orientations. The mechanical properties of such three-part nanocomposites are evaluated using EshelbyMori-Tanaka (EMT)'s technique. The coupled electromechanical governing equation of SMP under static loads is obtained by the estimation of displacement field with Reddy's third order theory (Reddy's TSDT) of plates. The coupled equation is also treated by developing a mesh-free solution to examine the impacts of embedding nanofillers and pores on the static electromechanical deflection and stress responses of SMP5. The results reveal that embedding pores up to around 90% of the volume of the middle plate leads to only 11.3% and 2.2% increase in mechanical and electrical deflections, respectively. Moreover, due to the formation of CNTs agglomerations, enhancing the middle plate with CNTs has a sharp positive impact on the reduction of deflections only up to some limited values of CNT volume fractions.
Keywords: Smart multidisciplinary plates; Piezoceramic faces; CNT agglomerations; Embedded pore; Static electromechanical loads